“Un sol di paradiso”. I soffitti all’antica di palazzo Medici a Firenze - Funis, Francesca (Opus Incertum, 2018)
This paper clarifies the historical constructive aspects of two 15th century wooden ceilings of the Medici palace (later Riccardi): the ceiling of the great hall and that of the Magi chapel. An hitherto unknown documentation from the Archive of the Opera of Santa Maria del Fiore, establishes the dating of timber works in the building yard (January 1449 - February 1451), and explains the methods of supply, origins and quantities of the wood purchased by Cosimo the Elder for the palace. The two ceilings are among the first coffered ceilings carved the "ancient" way. Their novelty consists in the shape but also in the use of double composite beams to support the coffers: this technical device was so new in Florence at the period that it required the shipment of a wooden model of a beam (1451) from Ferrara. Finally, the study explains how the restoration and consolidation of the great hall ceiling throughout the centuries has completely transformed the original structure: the works carried out by the Riccardi family (1660) more than halved the size of the ceiling, and gave it a different pictorial decoration, now entirely removed after the recent pictorial restoration (1998) aimed at restoring the Fifteenth Century aspect to the ceiling.